Perineural Invasion and Risk of Lethal Prostate Cancer - Zareba, Piotr; Flavin, Richard; Isikbay, Masis; Rider, Jennifer R; Gerke, Travis A; Finn, Stephen; Pettersson, Andreas; Giunchi, Francesca; Unger, Robert H; Tinianow, Alex M; Andersson, Swen-Olof; Andrén, Ove; et al. (Cancer epidemiology, biomarkers & prevention, 2017)
Prostate cancer has a propensity to invade and grow along nerves, a phenomenon called perineural invasion (PNI). Recent studies suggest that the presence of PNI in prostate cancer has been associated with cancer aggressiveness. We investigated the association between PNI and lethal prostate cancer in untreated and treated prostate cancer cohorts: the Swedish Watchful Waiting Cohort of 615 men who underwent watchful waiting, and the U.S. Health Professionals Follow-Up Study of 849 men treated with radical prostatectomy. One pathologist performed a standardized histopathologic review assessing PNI and Gleason grade. Patients were followed from diagnosis until metastasis or death. The prevalence of PNI was 7% and 44% in the untreated and treated cohorts, respectively. PNI was more common in high Gleason grade tumors in both cohorts. PNI was associated with enhanced tumor angiogenesis, but not tumor proliferation or apoptosis. In the Swedish study, PNI was associated with lethal prostate cancer [OR 7.4; 95% confidence interval (CI), 3.6-16.6; < 0.001]. A positive, although not statistically significant, association persisted after adjustment for age, Gleason grade, and tumor volume (OR 1.9; 95% CI, 0.8-5.1; = 0.17). In the U.S. study, PNI predicted lethal prostate cancer independent of clinical factors (HR 1.8; 95% CI, 1.0, 3.3; =0.04). These data support the hypothesis that perineural invasion creates a microenvironment that promotes cancer aggressiveness. Our findings suggest that PNI should be a standardized component of histopathologic review, and highlights a mechanism underlying prostate cancer metastasis. .